A Retrospective Analysis of the Clinical and Epidemiological Characteristics of COVID-19 Patients in Henan Provincial People's Hospital, Zhengzhou, China - Zhao, Jing; Gao, Hao-Yu; Feng, Zi-Yi; Wu, Qi-Jun (Frontiers in Medicine, 2020)
Objective: This study evaluated the clinical and epidemiological characteristics of patients with confirmed coronavirus disease 2019 (COVID-19). Methods: This retrospective study evaluated 29 patients with confirmed COVID-19 infection admitted to Henan Provincial People’s Hospital between January 27 and February 27, 2020, with follow-up until April 01, 2020. Results: The median age of the patients was 56 years. Nineteen (19/29; 65.5%) had underlying conditions including cardiovascular disease, digestive disease, or type 2 diabetes mellitus. Twenty-two (22/29; 76%) had close contact with acquaintances or family members who were confirmed or probable COVID-19 cases. Many patients had white blood cell counts with abnormal neutrophil and lymphocyte numbers; abnormal hemoglobin concentration, coagulation profiles, and blood biochemistry, and increased infection markers. Mottling and multiple ground-glass opacities were seen in X-ray images of 19 patients (19/29; 65.5%). Most patients (23/29; 79.8%) received supplemental oxygen therapy and antibiotics (23/29; 79.8%) in addition to traditional Chinese medicines (26/29; 89.7%). The most frequent presenting symptoms were fever, cough, and sputum production. One patient, an 86-year-old woman with more than one underlying disease died during follow-up. Patients with severe disease were significantly older and more likely to have been transferred from other healthcare facilities than those with mild disease. Anemia, decreased activated partial thromboplastin time, calcium, and albumin, and increased D-dimer and interleukin-6 were more frequent in severe disease. Need of oxygen therapy, mechanical ventilation, intravascular immunoglobulin, and duration of antibiotic therapy were increased in those with severe disease. Conclusions: Significant differences in demographical and clinical characteristics were observed in patients with moderate and severe COVID-19.